Analyzing the impact of ergonomics, biodegradability, and material science on consumer behavior in food packaging - Nelfiyanti, Nelfiyanti; Ernyasih, E.; Nugrahani, Ratri Ariatmi; Nik Mohd Zuki, Nik Mohamed; Setiawan, Andry; Muhammad Aditia, Al-Hafidz; Daruki, D. (Universiti Malaysia Pahang, 2025)
Food packaging performs the important functions of protecting the product and influencing consumer behavior whilebeing convenient and sustainable.There have been few studies that thoroughly debated the role of ergonomics, biodegradability, and material science in shaping consumer behavior toward buying behavior. The problem has come into the spotlight as consumers increasingly look for not only functional, but sustainable and convenient packaging. Thus, in this research, the effects of ergonomic design, biodegradability, chemical and mechanical physics on organizational purchase intention will be investigated. Partial LeastSquares Structural Equation Modeling was used to analyze the data from 121 respondents. Analysis Period Initial Rows Thefour variables explained 62.8% of the variance in purchase intention (R² = 0.628), the strongest variable was biodegradability (F² = 0.140), followed by ergonomics (F² = 0.115)). The fields of physical mechanics and physical chemistrywere significantly relevant to this study, as per its study findings. The study results made certain that all presumptions were accurate, three-polite, eccellenzeof expertise in sustainable, easy-to-use packaging, form consumer choice to purchase. Thus,out of these conclusions I realized that packaging design is not just being efficient in accomplishing the economic behind packaging, it has to accomplish the genuine human needs of consumers —for practicality and convenience. It indicates that actual innovation in packaging does not emanate from merely trend chasing or where the winds blow, it comes from a good grasp of what the marketplace is actually looking for.